2000
DOI: 10.1021/la991024q
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Properties and Interface Dynamics:  Time Evolution of Spinodal Interface in a Binary Polymer Mixture at the Critical Composition

Abstract: The time-evolution of a three-dimensional (3D), bicontinuous interface of a phase-separated polymer mixture in the late stage spinodal decomposition (SD) process has been studied by laser scanning confocal microscopy (LSCM) and time-resolved light scattering. The time evolution of the interface between two coexisting phases developed via SD ("spinodal interface") was quantitatively captured in 3D by using LSCM. On the basis of the differential geometry, probability densities of the local curvatures, i.e., the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…More recent numerical simulations confirmed this scaling behavior, and provided some insights about the geometry in real space [10][11][12]. Meanwhile, access to direct space was made possible by new techniques of observation, such as scanning laser confocal microscopy: curvatures could be measured on phase-separated polymer blends [13,14]. These observations are especially relevant to discuss the local mechanisms that govern the coarsening: pinch-off was for instance observed in a colloidal glass [15].…”
mentioning
confidence: 86%
“…More recent numerical simulations confirmed this scaling behavior, and provided some insights about the geometry in real space [10][11][12]. Meanwhile, access to direct space was made possible by new techniques of observation, such as scanning laser confocal microscopy: curvatures could be measured on phase-separated polymer blends [13,14]. These observations are especially relevant to discuss the local mechanisms that govern the coarsening: pinch-off was for instance observed in a colloidal glass [15].…”
mentioning
confidence: 86%
“…Curvature analysis is becoming increasing useful for structure analysis and classification for phase separation structure, 23,24 since three-dimensional observation by laser scanning confocal microscopy and numerical simulation can be applied to the field of morphological research in condensed matter. We wish to introduce such perspective for the morphology of the TPE/oil system.…”
Section: Comparison With Other Conceptmentioning
confidence: 99%
“…[5][6][7][8][9] However, in the past five years, several studies have reported on direct observation of phase separation phenomena using laser scanning confocal microscopy, e.g., Ribbe, 10 Jinnai, 11,12 and Hermansson. 13 Recently, the authors proposed new non-aqueous physical gels prepared with small proportions of semicrystalline thermoplastic elastomers (nearly 10 wt% polymer concentration) and large proportions of oils of low molecular weight.…”
mentioning
confidence: 99%
“…5 Although the kinetics of earlyto late-stage phase separation have been studied in considerable detail, [8][9][10] the kinetics of the initial stage (formation of concentration fluctuations from the uniform state) are not as well understood. In addition, the solvent-casting process, which is commonly used in making films, often accompanies the phase separation.…”
Section: Introductionmentioning
confidence: 99%